Nonviolence in Our Abortion Discourse? A Postelection Opening - Camosy, Charles C. (Horizons, 2013)
Some believe that there is no hope for moving beyond the culture wars in the United States—especially when they are connected to the persistently difficult abortion debate. This article argues, however, that the situation is more hopeful than most realize. The imagined "choice" and "life" camps do not map onto the complex reality of public opinion, especially among the Millennials. This article contends that "nonviolence" is an important common value for different kinds of people who imagine themselves to be on very different sides in the abortion debate. When applied consistently to rhetoric, individual persons and bodies, and social structures, a commitment to nonviolence not only provides an opening for productive and authentic discussion but also highlights broad areas of agreement and common ground.